2020
DOI: 10.1038/s41419-020-2425-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel tumor angiogenesis inhibitor targeting Shh/Gli1 signaling pathway in Non-small cell lung cancer

Abstract: Although angiogenesis inhibitors targeting VEGF/VEGFR2 have been applied for tumor therapy, the outcomes are still unsatisfactory. Thus, it is urgent to develop novel angiogenesis inhibitor for cancer therapy from new perspectives. Identification of novel angiogenesis inhibitor from natural products is believed to be one of most promising strategy. In this study, we showed that pristimerin, an active agent isolated from traditional Chinese herbal medicine Celastrus aculeatus Merr, was a novel tumor angiogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…GANT-61, which interferes with GLI1 binding, inhibited mesodermal commit- xenograft models. 54 With regard to osteogenesis, studies in mice demonstrated that GLI1 can induce early osteoblast differentiation during bone formation. 43 Furthermore, GLI1 regulates mature bone metabolism by promoting osteoblast differentiation and repressing osteoblast maturation toward osteocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GANT-61, which interferes with GLI1 binding, inhibited mesodermal commit- xenograft models. 54 With regard to osteogenesis, studies in mice demonstrated that GLI1 can induce early osteoblast differentiation during bone formation. 43 Furthermore, GLI1 regulates mature bone metabolism by promoting osteoblast differentiation and repressing osteoblast maturation toward osteocytes.…”
Section: Discussionmentioning
confidence: 99%
“…GANT‐61, in addition to its apoptotic and antiangiogenic effects, also reduces stem cell markers in cancer cells 53 . Furthermore, SHH/GLI inhibitors other than GANT‐61 also suppress tumor angiogenesis and tumor growth in xenograft models 54 …”
Section: Discussionmentioning
confidence: 99%
“…Pristimerin treatment has been reported to inhibit Shh-induced endothelial cellular essential processes during angiogenesis, with a concomitant abrogation of Shh-induced pericytes recruitment to the new blood vessels which is crucial for the maturation of blood vessels. Besides, Gli1 nucleus distribution in endothelial cells and pericytes was also repressed upon pristimerin treatment (17).…”
Section: Effects On Shh/gli1 Pathway: Inhibiting Angiogenesismentioning
confidence: 92%
“…The first research hotspot is multi-targeted molecular and biological mechanisms associated with pristimerin treatment in cancers. Various targets and pathways are involved in pristimerin treatment, including EGFR/HER2 (38), IGF-1R (23), PI3K/AKT pathway (105), NF-kB pathway (43), ROS generation (28), MAPK pathway (27), EphB4/CDC42/N-WASP pathway (19), Wnt/b-catenin pathway (22), Shh/Gil1 pathway (17), HIF-1a/SPHK-1 pathway (24), Micro RNA (9), proteasome (25), telomerase (26), etc. These molecular events ultimately determine tumor cell fates including cell cycle arrest, apoptosis, autophagy, migration, invasion, metastasis, EMT, CSCs, angiogenesis, etc.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
See 1 more Smart Citation